Analysis of Problem Solving Ability and Self-Efficacy of Junior High School Students - Widiastuti Widiastuti; Tina Rosyana; Euis Eti Rohaeti (Universitas Nusantara PGRI Kediri, 2018)
Abstract: This study aims to describe the ability of mathematical problem solving, student self-efficacy and the relationship between problem-solving ability and self-efficacy of junior high school students in Social Arithmetic materials. This research is descriptive quantitative-qualitative research. Subjects in this study were grade VIII students in West Bandung regency with a sample of 36 students of class VIII-B in one school in West Bandung regency. Instruments used in this study (1) problem solving problem test in the form of a description of four questions with social arithmetic material; (2) self-efficacy questionnaire counted twenty questions. Based on the analysis of data obtained shows that the ability of problem solving junior high school students in one district of West Bandung based on existing indicators are categorized as low and students' self-efficacy in solving math problems in moderate, so there is no relationship between problem-solving ability and self-efficacy. This is supported by the result of pearson correlation analysis which shows more than 0.05 significance number is 0.991 which means there is no relationship between the two variables.